Le rôle de la charia dans le contrôle et la détermination de l’efficacité des marchés financiers islamiques - Matar Alamatiri, Fahd (Finance and Business Economies Review, 2019)
This study aims at demonstrating the role played by the Shariah controls and determinants approved by the Islamic Sharia in achieving the efficiency of Islamic financial markets, and access to efficient and fair financial markets. Determining the prices of supply and demand forces without external interference.This study also showed ways to address many of the reasons that lead to the inefficiency of financial markets.These controls prevent the control of any party by the mechanisms of the market, and ensure the freedom of market participants, and provide sound information on the market. There are also controls designed to achieve the depth of the financial market The study recommended the need for clear and codified mechanisms to apply the determinants of the market in the form of laws to prevent them from exceeding, and sensitizing dealers in those markets the need to adhere to the determinants of legitimacy that benefit all dealers.